After Khomeini : Iran under his successors - Arjomand, Said Amir (Oxford University Press, 2009)
For many Americans, Iran is our most dangerous enemy--part of George W. Bush's "axis of evil" even before the appearance of Ahmadinejad. But what is the reality? How did Ahmadinejad rise to power, and how much power does he really have? What are the chances of normalizing relations with Iran? In After Khomeini, Said Amir Arjomand paints a subtle and perceptive portrait of contemporary Iran. This work, a sequel to Arjomand's acclaimed The Turban for the Crown, examines Iran under the successors of Ayatollah Khomeini up to the present day. He begins, as the Islamic Republic did, with K